Signaling in the Physiology and Pathophysiology of Pancreatic Stellate Cells – a Brief Review of Recent Advances - Kusiak, Agnieszka A.; Szopa, Mateusz D.; Jakubowska, Monika A.; Ferdek, Pawel E. (Frontiers in Physiology, 2020)
The interest in pancreatic stellate cells (PSCs) has been steadily growing over past two decades, predominantly because of their central role in the desmoplastic reaction associated with diseases of the pancreas, such as pancreatic cancer. In recent years, the scientific community devoted substantial efforts to understanding signalling pathways that govern PSC activation and interactions with neoplastic cells. This mini review aims to summarise some very recent findings on signalling in PSCs and highlight their impact to the field.